Advances in cell coculture membranes recapitulating in vivo microenvironments. Issue 2 (February 2023) - Yoo, Jin; Jung, Youngmee; Char, Kookheon; Jang, Yeongseon
Abstract : Porous membranes play a critical role in in vitro heterogeneous cell coculture systems because they recapitulate the in vivo microenvironment to mediate physical and biochemical crosstalk between cells. While the conventionally available Transwell® system has been widely used for heterogeneous cell coculture, there are drawbacks to precise control over cell–cell interactions and separation for implantation. The size and numbers of the pores and the thickness of the porous membranes are crucial in determining the efficiency of paracrine signaling and direct junctions between cocultured cells, and significantly impact on the performance of heterogeneous cell cultures. These opportunities and challenges have motivated the design of advanced coculture platforms through improvement of the structural and functional properties of porous membranes. Highlights: Advances in heterogeneous cell coculture systems using semi-permeable membranes have made it feasible to create in vivo -like microenvironments for a myriad of biomedical applications. The development of in vitro cell coculture systems facilitates our understanding of cell–cell interactions in tumors and stem cell differentiation. Engineered coculture membranes play a significant role in heterogeneous coculture systems for drug testing, tissue barrier modeling, and tissue engineering, to name a few. Rational design and engineering of porous membranes will bridge the gap between in vitro experiments and in vivo applications.